Värmebehandlat trä : att inhämta synpunkter i produktutvecklingens tidiga fas - Trulson, Mattias (SLU/Dept. of Forest Products, 2008)
This study is a part of a Swedish research and development project that is about heat-treated wood and is led by the Swedish University of Agricultural Sciences and Luleå University of Technology. Products that are heat-treated already exists on the market, foremost the Finnish brand ThermoWood®, bur the project group want to find out if it would be possible to start a Swedish production with somewhat different applications than what is common today. The heat-treated wood has many attributes that have changed in the heating process. It becomes more biologically durable, it gains stability in form and dimensions and it becomes darker and looses several unwanted extractives such as resin. Disadvantages that can be mentioned are that the wood becomes fragile and the strength properties changes.